Sublethal doses of fipronil intensify synapsin immunostaining in Atta sexdens rubropilosa (Hymenoptera: Formicidae) brains - Cintra-Socolowski, Priscila [UNESP]; Roat, Thaisa C. [UNESP]; Nocelli, Roberta C. F.; Nunes, Pablo H. [UNESP]; Ferreira, Rafael A. C. [UNESP]; Malaspina, Osmar [UNESP]; Bueno, Odair C. [UNESP] (Wiley-Blackwell, 2016)
BACKGROUNDAlthough ants are common insects in agricultural ecosystems, few studies have considered how xenobiotics might induce physiological and morphological alterations in these insects. This study aimed to verify the neurotoxic action of sublethal doses of fipronil on the mushroom bodies of brains from the leaf-cutting ant Atta sexdens rubropilosa through immunocytochemistry analysis for the protein synapsin. RESULTSThe LD50 value was established as 1.42ng ant(-1), and the sublethal doses used were LD50/10 and LD50/100. Synapsin labelling was more evident in the brains extracted from ants exposed to the insecticide, specifically in the regions of glia in the mushroom bodies, compared with the control group. It was possible to measure the intensity of emitted fluorescence in the areas of the mushroom bodies, and a statistical test showed differences between the control group and the treatment group. CONCLUSIONThus, it is concluded that sublethal doses of the insecticide fipronil intensified synapsin immunostaining, suggesting an increased release of neurotransmitters, which may be linked to neurotoxicity and overexcitation. These sublethal doses may have two different effects: compromising the operation and maintenance of the colony and leading to the establishment of resistance in insects. (c) 2015 Society of Chemical Industry
Keywords: mushroom body; olfactory; visual; leaf-cutting ants; Hymenoptera